The Effect of Financial Ratios on Financial Distress Conditions in Sub Industrial Sector Company - Restianti, Tya; Agustina, Linda (Universitas Negeri Semarang, 2018)
This study aimed to analyze the influence of financial ratios proxied by the current ratio, the retained earnings to total assets, earnings before interest and tax to total assets, return on equity, debt to assets ratio, and total assets turnover against Financial distress. The population in this study is a sub company of various industry listed in Indonesia Stock Exchange (IDX) in the period from 2013 to 2015 with the number of 40 companies. The sampling technique used purposive sampling technique and acquired 35 companies with 105 units of analysis. Data were analyzed with descriptive statistics and logistic regression. These results indicate that earnings before interest tax to total assets and return on equity have an impact on financial distress. While the current ratio, the retained earnings to total assets, debt to assets ratio, and total assets turnover has no influence on the financial company’s distress. The conclusion of this research is that the company’s financial distress condition can be avoided by reducing the financing coming from debt. In addition, increasing sales and maximizing the use of assets and equities that companies have can also reduce and avoid the company from financial distress.